2019
DOI: 10.3390/metabo9010011
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Metabolic Pathways in Osteoarthritis

Abstract: Sir Archibald Edward Garrod, who pioneered the field of inborn errors of metabolism and first elucidated the biochemical basis of alkaptonuria over 100 years ago, suggested that inborn errors of metabolism were “merely extreme examples of variations of chemical behavior which are probably everywhere present in minor degrees, just as no two individuals of a species are absolutely identical in bodily structure neither are their chemical processes carried out on exactly the same lines”, and that this “chemical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 62 publications
2
56
0
Order By: Relevance
“…The presence of a lysoPC negatively correlated with a number of PCs indicates that an alteration of the PC to lysoPC conversion, and thus an increase of downstream inflammatory mediators produced through this conversion, could be associated with function non-responders. Carnitine, another metabolite in this network, has also previously been associated with OA; two separate studies have shown decreased serum levels of acylcarnitines to be associated with OA patients, potentially due to impairment of chondrocyte repair (Zhai 2019). A connection has also previously been established between threonine and carnitine; in a rat model fed with a diet deficient in lysine and threonine, skeletal muscles became deficient in carnitine (Khan and Bamji 1979).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The presence of a lysoPC negatively correlated with a number of PCs indicates that an alteration of the PC to lysoPC conversion, and thus an increase of downstream inflammatory mediators produced through this conversion, could be associated with function non-responders. Carnitine, another metabolite in this network, has also previously been associated with OA; two separate studies have shown decreased serum levels of acylcarnitines to be associated with OA patients, potentially due to impairment of chondrocyte repair (Zhai 2019). A connection has also previously been established between threonine and carnitine; in a rat model fed with a diet deficient in lysine and threonine, skeletal muscles became deficient in carnitine (Khan and Bamji 1979).…”
Section: Discussionmentioning
confidence: 93%
“…The negative correlation between glutamine and PCs also overlapped between these two networks. Glutamine plays a role in a number of metabolic pathways and glutaminolysis can eventually lead to fatty acid production through a number of pathways including the TCA cycle (Curi et al 2017), which has been implicated to be altered in OA (Zhai 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the pro‐inflammatory genes regulated by NF‐κB, such as tumor necrosis factor α, interleukin‐1β, and cyclooxygenase‐2 (COX‐2), play important roles in pain regulation . COX‐2 is an integral enzyme in the production of eicosanoids, which are themselves downstream products of PC metabolism due to the release of arachidonic acid, the precursor of eicosanoids, during the conversion of PC to lysoPC by phospholipase A 2 . Both NF‐κB and COX‐2 have been reported to be involved in OA; NF‐κB signaling induces hypertrophy in chondrocytes, promotes synovitis and cartilage degradation, and alters resorption of bone, leading to abnormal bone formation .…”
Section: Discussionmentioning
confidence: 99%
“…40 COX-2 is an integral enzyme in the production of eicosanoids, 33 which are themselves downstream products of PC metabolism due to the release of arachidonic acid, the precursor of eicosanoids, during the conversion of PC to lysoPC by phospholipase A 2 . 41 Both NF-κB and COX-2 have been reported to be involved in OA; NF-κB signaling induces hypertrophy in chondrocytes, promotes synovitis and cartilage degradation, and alters resorption of bone, leading to abnormal bone formation. 42 COX-2, meanwhile, is an important target for pain management in OA, with many NSAIDs suggested for OA patients targeting COX-2 and limiting the pro-inflammatory effects of its enzymatic products.…”
Section: Journal Of Orthopaedic Researchmentioning
confidence: 99%
“…In our study, we observed that the prominent changes in KOA rats in TAGs, DAG, PC, LPC, PE, and FAHFAs, with the greatest change observed in TAGs. Most scholars consider KOA a systemic disease, and many studies have shown that there is a certain correlation between metabolic syndrome and OA, hypertension and that glucose and lipid metabolism disorders can promote the development of OA [27,28]. Many studies have shown a positive correlations between both TAGs and DAG and KOA [29]: this finding was slightly unique, and that study contradicted this finding.…”
Section: Discussionmentioning
confidence: 95%